2016
DOI: 10.20853/30-2-606
|View full text |Cite
|
Sign up to set email alerts
|

An employee engagement framework for technical vocational education and training colleges in South Africa

Abstract: Employee engagement refers to what takes place when people are interested in a positive way and when they are excited about their jobs, exercise discretionary behaviour and are motivated to achieve high levels of performance. The present research therefore examined employee engagement of the academic staff in the Technical Vocational Education and Training (TVET) Colleges in South Africa. A quantitative design was used. In total, 2 054 academic staff completed the questionnaire. A self-administered 4-point Lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…However, with only about 10 000 academic staff, the current enrolments (660 000) mean a staff: student ratio that is antithetic to quality service (Mmako & Schultz, 2016). Furthermore, in 2009, the old NATED courses were reintroduced and TVETs now have to cope with both the old NATED and new NCv courses, which also throws into question their ability to cope with an increasingly complex situation (Mmako & Schultz, 2016). Unfortunately, very little research has been conducted into these issues and it thus appears as if little is being done to improve the situation at TVET colleges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, with only about 10 000 academic staff, the current enrolments (660 000) mean a staff: student ratio that is antithetic to quality service (Mmako & Schultz, 2016). Furthermore, in 2009, the old NATED courses were reintroduced and TVETs now have to cope with both the old NATED and new NCv courses, which also throws into question their ability to cope with an increasingly complex situation (Mmako & Schultz, 2016). Unfortunately, very little research has been conducted into these issues and it thus appears as if little is being done to improve the situation at TVET colleges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almost all research on the academic research supervisors' role focuses on conscious behaviour from a behaviouristic, humanistic, social and positive psychology perspective and using quantitative research (Mmako and Schultz 2016). For example, Govender and Ramroop (2013) found that supervisors' perception of organisational climate influences their perception of the quality of the supervision.…”
Section: Academic Research Supervisionmentioning
confidence: 99%
“…TVET is essential in relinquishing an intense qualification and will be able to fill jobs and prepare for this Industry 4.0 (Zulkifli et al, 2020) with students' technical and soft skills (Kayode, Noordin, & Wahid, 2020). However, TVET confronts main contests for recruiting and retaining talented lecturers in academic and teaching (Bălan, 2019;Clayton & Harris, 2019;Mmako & Schultz, 2016). Yet, lecturers now realized themselves facing escalating pressure to familiarise classroom instruction to adapt for contemporary and embryonic technologies (Waters & Hensley, 2020) and enhance graduate employability and teaching which included skills-oriented and vocational training (Macheridis, Paulsson, & Pihl, 2020) This is imputable to the high burden of work among lecturers at TVET colleges bringing numerous and heavy pressure (Pellerone, Rapisarda, Trischitta, Vitale & Ramaci, 2020) and low organizational commitment amongst lecturers (Shafiq & Akram Rana, 2016;Barkhuizen, Rothman & Van de Viljver, 2014).…”
Section: Introductionmentioning
confidence: 99%